Challenges faced by students with hearing impairment in Bulawayo urban regular schools - Gudyanga, Ephias; Wadesango, N.; Hove, Eliphanos; Gudyanga, Anna (MCSER Publishing, 2016)
There is a risk of students with hearing impairment being excluded from the teaching and learning that goes on, unless measures are taken to make sure they are fully included. This prompted this desktop study on problems associated with the inclusion of hearing impaired students in secondary schools. The study established that besides communication problems, students experienced feelings of anger, frustration and isolation depending on the dictates of the environment. Literature revealed that learning is a process that happens under observable and ideal conditions to the extent that situations in which students are placed deliberately or otherwise had great effects on them. The review of literature focused on the problem and its context. It also emerged that there was an opportunity for teachers and other stakeholders to reflect on their school and classroom practices with hearing impaired students and adopt effective strategies of managing them in inclusive secondary schools.